A prospective cohort study of pain with intrauterine device insertion among women with and without vaginal deliveries. (April 2014) - Allen, R. H.; Carey, M. S.; Raker, C.; Goyal, V.; Matteson, K.
Abstract The purpose of this prospective cohort study was to compare pain during IUD insertion between women with a history of vaginal delivery and women without a history of vaginal delivery. First-time IUD users chose either the CuT380A or the levonorgestrel IUS. We enrolled 49 women with previous vaginal delivery and 49 women with no history of vaginal delivery (either only caesarean deliveries or nulliparous). The mean pain score on a 0–100 mm visual analog scale during insertion in the vaginal delivery group was 34.7 (SD 31.6) compared with 51.2 (SD 29.2) in the group without previous vaginal delivery (p = 0.009). In multivariable analysis controlling for age, breast-feeding, expected pain, baseline anxiety, insertion timing (6–12 weeks postpartum, 2–4 weeks post-abortion or interval), and insertion difficulty, history of vaginal delivery was associated with a 15.5 point reduction in pain (95% CI, –27.4, –3.7). Other significant predictors of pain were 'expected pain' and 'insertion difficulty'.